Role of gastrograffin in adhesive bowel obstruction after unsuccessful conservative treatment: a prospective evaluation - Maharjan, Suresh; Manandhar, Kishor; Singh, Binita; Shakya, Niliza; Patel, Om P. (International Surgery Journal, 2024)
Background: Water soluble gastrograffin (GG) administration via nasogastric (NG) tube has shown to resolve the obstructive features and reduced the need for surgery and reduced hospital stay in the patients presenting with adhesive small bowel obstructions (ASBOs). Thus the use of GG in patients who did not improve after 48 hours of conservative treatment was found to be very useful in the management of ASBOs. Methods: 77 patients presenting with the features of ASBOs in Department of General Surgery, Bir Hospital were included in the study which took place from July 2021 to April 2022. Those patients who presented with the signs of strangulation, peritonitis, complete obstruction and clinical signs of large bowel obstruction were excluded from the study. Results: The mean time at which the symptoms of abdominal pain resolved was 17.45 hours, 28.5 hours and 23.06 hours in patients improved with conservative management, with GG and who undergone surgery respectively. The mean time for passage of flatus was 57.42 hours in patients treated with GG. The mean time in which the patients passed stool was 36.92 hours, 66 hours and 74.8 hours in patients treated with conservative treatment, GG and operated respectively. It took 50.81 hours, 81.68 and 95.4 hours for improvement with conservative management, GG and surgery respectively. Conclusions: The administration of GG in ASBOs after the failure of the initial 48 hours conservative management of ASBOs reduced the need for operative procedures and number of hospital days as most of them did not require surgery.